Correction: Physical modeling of the effect of shape, blockage, and flow variability on scour in culvert outlets. - Kaywan Othman Ahmed; Mohammad Reza Kavianpour; Ata Amini; Younes Aminpour (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0306252.].